Effectiveness of Space Spraying on the Transmission of Dengue/Dengue Hemorrhagic Fever (DF/DHF) in an Urban Area of Southern Thailand - Suwich Thammapalo; Supaporn Meksawi; Virasakdi Chongsuvivatwong (Journal of Tropical Medicine)
Timely and extensive space spraying has been widely used to prevent the spread of dengue fever/dengue hemorrhagic fever (DF/DHF). Field evaluations on its effectiveness have been rarely reported. This study aimed to evaluate the timeliness, coverage, and effectiveness of space spraying for DF/DHF control using a geographic information system (GIS). Longitudinal monitoring of DF/DHF cases and spray activities in Songkhla municipality was done between May 2006 and April 2007. After a case was detected, subsequent cases occurring within a 100 meter radius of the index case’s house and between 16–35 days of onset were considered as potential secondary cases. During the study period, 140 cases of DF/DHF were detected. Of these, 25 were identified as secondary infections from 20 index cases. Where a secondary infection occurred, the mean attack rate was 2.7 per 1,000 population. Two significant predictors for being a secondary case were both related to the house of the index case, namely, absence of window screens and being constructed with corrugated iron sheets. Our findings suggest that space spraying in the study area was inadequate and often failed to prevent secondary cases of DF/DHF. Control programs should target houses constructed with corrugated iron sheets.